Representing Glaciations and Subglacial Processes in Hydrogeological Models: A Numerical Investigation - Arnaud Sterckx; Jean-Michel Lemieux; Rein Vaikmäe (Geofluids)
The specific impact of glacial processes on groundwater flow and solute transport under ice-sheets was determined by means of numerical simulations. Groundwater flow and the transport of δ18O, TDS, and groundwater age were simulated in a generic sedimentary basin during a single glacial event followed by a postglacial period. Results show that simulating subglacial recharge with a fixed flux boundary condition is relevant only for small fluxes, which could be the case under partially wet-based ice-sheets. Glacial loading decreases overpressures, which appear only in thick and low hydraulic diffusivity layers. If subglacial recharge is low, glacial loading can lead to underpressures after the retreat of the ice-sheet. Isostasy reduces considerably the infiltration of meltwater and the groundwater flow rates. Below permafrost, groundwater flow is reduced under the ice-sheet but is enhanced beyond the ice-sheet front. Accounting for salinity-dependent density reduces the infiltration of meltwater at depth. This study shows that each glacial process is potentially relevant in models of subglacial groundwater flow and solute transport. It provides a good basis for building and interpreting such models in the future.